Tomographic Imaging of the Agung-Batur Volcano Complex, Bali, Indonesia, From the Ambient Seismic Noise Field - Zulfakriza, Zulfakriza; Nugraha, Andri D.; Widiyantoro, Sri; Cummins, Phil R.; Sahara, David P.; Rosalia, Shindy; Priyono, Awali; Kasbani, Kasbani; Syahbana, Devy K.; Priambodo, Imam C.; Martanto, Martanto; Ardianto, Ardianto; et al. (Frontiers in Earth Science, 2020)
The Agung-Batur Volcanic Complex (ABVC), part of the Sunda volcanic arc, is the source of some of the most hazardous volcanic activity in Indonesia. The ABVC has undergone many small (VEI 1-2) eruptions since historical records began in the early 19th century, but Mt. Agung has experienced much larger (VEI 5) eruptions, both in the modern (1963) and historical (1843) eras, as well as several times during the past 2000-3000 years. The 1963 eruption caused more than 1000 deaths, and a more recent eruption in 2017 caused the evacuation of 140,000 people. Delineating the magma structure beneath ABVC is an important first step in understanding the physics of these eruptions. This paper presents the first local-scale study of Rayleigh wave group velocity structure and the seismic velocity structure beneath the ABVC using ambient seismic noise tomography. Seismic data were collected using 25 seismometers deployed across the ABVC during early January to March 2019. The local seismic network provides good resolution beneath both Mt. Agung and Mt. Batur. We obtained 158 Rayleigh Green’s Functions, extracted by cross correlating noise simultaneously recorded at available station pairs. We used sub-space inversion to calculate group velocity at different periods and to estimate the lateral variations in group velocity for given periods. 2-D tomographic maps obtained from the inversion of the group velocity of Rayleigh waves clearly showed some pronounced velocity anomalies beneath the ABVC. We applied the Neighbourhood Algorithm (NA) technique to invert the Rayleigh wave dispersion curves to obtain shear wave velocity (Vs) vs. depth profiles. These profiles indicate a low Vs of about 1 km/s underlying the volcanic complex between Mt. Agung and Mt. Batur at depths up to 2 km, which we suggest is due to a combination of low-Vs volcanic deposits as well as a shallow hydrothermal fluids system associated with magma fluids and/or gases produced by magma intrusion at depths > 7 km.